Uwagi Wittgensteina "O pewności" a teoria kolektywów myślowych i stylów myślowych Flecka - Sady, Wojciech (Filozofia Nauki, 2019)
In his ‘Philosophical Investigations’, Wittgenstein declares that he is neither creating a theory nor explaining anything: he is merely describing the ways of using words and sentences, thus trying to make philosophical problems disappear. In fact, however, he proposes a theory of the nature of language games and their functions, even though — because of the above declaration — he expresses it in a fragmentary and unclear way. After 1946, his views underwent significant transformations: he abandoned the philosophy of mathematics for the philosophy of psychology. And in the last months of his life, in the notes published posthumously as On Certainty, he expressed a number of epistemological claims that explain our cognitive attitudes. He did not manage to finish this work. We have to do it for him, and crucial supplements are provided — as this paper argues — by Ludwik Fleck’s theory of thought collectives and thought styles.